Wholesaler echelon and Industry 4.0 in circular supply chains: A~systematic review - Lucas Conde Stocco; Luciana Oranges Cezarino; Lara Bartocci Liboni; V. G. Venkatesh (Modern Supply Chain Research and Applications, 2022)
Purpose - This paper aims to analyse systematically previous literature that sought to understand the formation of circular supply chains (CSCs) and propose a research agenda for implementing circular economy 4.0 in the wholesale industry. Design/methodology/approach - The research is based on a systematic literature review. Findings There is a prevalence of research related to manufacturing and how industrial complexes can establish practices linked to the circular economy. The reviewed papers in this study can be classified into three perspectives: systemic analysis, institutional perspective and operational perspective. Considering these categories and the wholesaler perspective, there is a scope to explore Industry 4.0 technologies applications with wholesale distributors and their contributions to the reverse flow of waste along the CSC. In addition, it is interesting to examine the interpretation of wholesale distributors on circularity, and how these members can contribute to filling the information gaps between industries and retailers based on the concepts of circular economy and Industry 4.0, and how they can contribute to establishing public policies for proper waste recycling methods. Originality/value - First, this research considers the wholesaler the exclusive supply chain member under the influence of Industry 4.0 and highlights its importance in firms' circular operations. Second, it provides an inclusive plan for the other stakeholders to interact with the wholesaler echelon to design and operate under 4.0 technologies to consolidate effective CSCs.
Keywords: 650; Closed-loop~supply chain; Distribution; Reverse logistics; Sustainability; Sustainable supply chain management; Wholesale